TIME CONSTRAINTS ON THE FORMATION OF THE KANDALAKSHA AND KERETSK GRABENS OF THE WHITE SEA PALEO-RIFT SYSTEM FROM NEW ISOTOPIC GEOCHRONOLOGICAL DATA - N. B. Kuznetsov; A. S. Baluev; E. N. Terekhov; S. Yu. Kolodyazhnyi; E. S. Przhiyalgovskii; T. V. Romanyuk; A. S. Dubensky; V. S. Sheshukov; S. M. Lyapunov; T. B. Bayanova; P. A. Serov (Геодинамика и тектонофизика, 2021)
Initially, the age and stratigraphic position of the Tersk formation were determined with respect to the fact that this formation overlaps the Early Proterozoic granitoids. Its top was marked by the rocks penetrated by the Late Devonian alkaline intrusions, including explosion pipes.This article presents the U-Pb isotopic dating of detrital zircon grains (dZr) from sandstones of the Tersk formation. It describes the geochemical compositions of the rocks and the Sm-Nd study results. In our study, the weighted average age of four youngest dZr grains from the sandstones of the Tersk formation is 1145±20 Ma, which suggests that the rocks above the studied rock layer (see the Tersk formation cross-section) are is not older than the end of the Middle Riphean. The U-Pb isotopic ages of dZr grains (provenance signals) from the sandstones of the Tersk formation were compared to the ages of other Upper Precambrian clastic strata in the northeastern East European platform (EEP) and adjacent areas. Our comparative analysis shows that these rocks significantly differ in age. This conclusion is in good agreement with the idea that at the end of the Middle and during the Late Riphean, several small (mainly closed) basins separated by uplifts dominated in the paleogeographic setting of the area wherein the White Sea rift system (WSRS) formed and developed. Temporal connections of these basins with the ocean were possible. Such paleogeographic setting does not favour the development of large rivers; this is why the grabens are mainly filled with local rock materials. The Keretsk and Kandalaksha grabens (WSRS) are filled with marine sediments eroded from the grabens walls. The local sediment sources include eclogite complexes (~1.9 Ga), which basic magmatism is dated at ~2.4–2.5 and ~2.7–2.9 Ga. Any potential primary sources for dZr grains are lacking in the area near the Keretsk graben. We suggest that such grains occurred due to recycling of the secondary sources of zircon, i.e. originated from ancient local sedimentary formations.